King : A Biography - Lewis, David Levering, 1936- (Book collections on Project MUSE., 2013)
Acclaimed by leading historians and critics when it appeared shortly after the death of Dr. Martin Luther King Jr., this foundational biography wends through the corridors in which King held court, posing the right questions and providing a keen measure of the man whose career and mission enthrall scholars and general readers to this day. Updated with a new preface and more than a dozen photographs of King and his contemporaries, this edition presents the unforgettable story of King's life and death for a new generation.